Implementation of suicide bereavement support: a scoping review - Nicholls, Tescha; Krysinska, Karolina; Reifels, Lennart; Kartal, Dzenana; Andriessen, Karl (Frontiers in Public Health, 2024)
IntroductionApproximately one in five people will experience a death by suicide during their lifetime. Struggling to understand their experiences, people bereaved by suicide often require formal support including support groups, online resources and discussion forums. While previous research has focused on examining experiences of grief, little is known about the implementation of support programs for people bereaved by suicide.MethodsAdhering to PRISMA-ScR guidelines, eight databases were searched for peer-reviewed studies that focused on the strategies or evaluation of the implementation of suicide postvention programs.ResultsSixteen studies met the eligibility criteria. A narrative synthesis of study findings mapped to the Proctor implementation framework shows that a variety of implementation outcomes have been assessed by different studies; however, there is limited use of formal implementation frameworks to guide analysis.DiscussionRecommendations from this review indicate the need for consistent terminology and better utilisation of implementation frameworks to guide postvention research and provide a well-rounded view of implementation. Increasing the use of reliable and validated tools to measure implementation outcomes will also increase the rigour of implementation research in this field.Systematic review registrationhttps://doi.org/10.17605/OSF.IO/4RB92.